Effectiveness of Spironolactone in Reducing Osteoporosis and Future Fracture Risk in Middle-Aged and Elderly Hypertensive Patients - Song S; Cai X; Hu J; Zhu Q; Shen D; Ma H; Zhang Y; Ma R; Yang W; Hong J; Zhang D; Li N (Dove Medical Press, 2024)
Shuaiwei Song,1- 5,* Xintian Cai,1- 5,* Junli Hu,1- 5 Qing Zhu,1- 5 Di Shen,1- 5 Huimin Ma,1- 5 Yingying Zhang,1- 5 Rui Ma,1- 5 Wenbo Yang,1- 5 Jing Hong,1- 5 Delian Zhang,1- 5 Nanfang Li1- 5 1Hypertension Center of People's Hospital of Xinjiang Uygur Autonomous Region, Urumqi, Xinjiang, 830001, People's Republic of China; 2Xinjiang Hypertension Institute, Urumqi, Xinjiang, 830001, People's Republic of China; 3NHC Key Laboratory of Hypertension Clinical Research, Urumqi, Xinjiang, 830001, People's Republic of China; 4Key Laboratory of Xinjiang Uygur Autonomous Region "Hypertension Research Laboratory", Urumqi, Xinjiang, 830001, People's Republic of China; 5Xinjiang Clinical Medical Research Center for Hypertension (Cardio-Cerebrovascular) Diseases, Urumqi, Xinjiang, 830001, People's Republic of China*These authors contributed equally to this workCorrespondence: Nanfang Li, Hypertension Center of People's Hospital of Xinjiang Uygur Autonomous Region, No. 91 Tianchi Road, Urumqi, Xinjiang, 830001, People's Republic of China, Tel +86 8,564,818, Email lnanfang2016@sina.comObjective: While the role of aldosterone in bone metabolism is well established, the specific effects of the widely used aldosterone antagonist, spironolactone, on bone health are not fully understood. This study aimed to investigate the effects of spironolactone on osteoporosis and future fracture risk in middle-aged and elderly hypertensive patients, revealing its potential benefits for bone health.Methods: Propensity score matching was employed in this study to create matched groups of spironolactone users and non-users at a 1:4 ratio. We investigated the association between spironolactone use and the risk of osteoporosis using multivariate logistic regression analysis. Furthermore, we conducted multivariate linear regression analysis to explore the relationship between cumulative dosage and the FRAX score. Subgroup analysis was also performed to assess the effects under different stratification conditions.Results: In both pre-match and post-match analyses, multivariable logistic regression revealed a significant reduction in the risk of osteoporosis in the spironolactone usage group (pre-match: odds ratios [OR] 0.406, 95% confidence interval [CI], 0.280- 0.588; post-match: OR 0.385, 95% CI, 0.259- 0.571). Furthermore, post-match multivariable linear regression demonstrated a clear negative correlation between cumulative spironolactone dosage and the FRAX score. Subgroup analyses consistently supported these findings.Conclusion: This study offers evidence supporting the significant positive impact of the antihypertensive drug spironolactone on bone health, resulting in a substantial reduction in the risk of osteoporosis and future fractures in hypertensive patients. Future research should consider conducting large-scale, multicenter, randomized controlled trials to further investigate the long-term effects of spironolactone on bone health in hypertensive patients.Keywords: hypertensive, spironolactone, aldosterone, osteoporosis, FRAX score